Numerical investigation for strengthened RC footings with square concrete jacketing. (June 2022) - Attia Fouda, Mohamed; Ibrahim, Amr; El-Kateb, Mahmoud; Elkateb, Tamer; Khalil, Ayman
Abstract: Strengthening of existing isolated footings using concrete jacketing is a traditional method to increase the load-carrying capacity and to enhance the performance of isolated footings. This paper presents a parametric study and a numerical validation for full-scale square footings strengthened with concrete jacketing, using either dowels and bonding agent or bonding agent only, to connect the existing and new concrete surfaces. A nonlinear finite element program "ABAQUS" was used for the numerical validation and the parametric investigation for various parameter's effect on the load-carrying capacity and contact stress redistribution underneath the strengthened footings. The parameters used in the parametric analysis include the ratio of the concrete jacket depth to the concrete footing depth, concrete compressive strength, spacing between dowels, and the ratio of the concrete jacket width to the concrete footing width. The effect of dowels on load carrying capacity of footings strengthened using a full concrete jacket is insignificant for jacket width smaller than the footing width. In footing strengthened using a full concrete jacket, the load carrying capacity increases by 9% compared to the non-strengthened footing.